Black Dragon Afro Asian Performance and the Martial Arts Imagination - Price, Zachary F. (The Ohio State University Press, 2022)
In Black Dragon, Zachary F. Price illuminates martial arts as a site of knowledge exchange between Black, Asian, and Asian American people and cultures to offer new insights into the relationships among these groups. Drawing on case studies that include Kareem Abdul-Jabbar's appearance in Bruce Lee's film Game of Death, Ron Van Clief and the Black Panther Party for Self-Defense, the Wu-Tang Clan, and Chinese American saxophonist Fred Ho, Price argues that the regular blending and borrowing between these distinct cultural heritages is healing rather than appropriative. His analyses of performance, power, and identity within this cultural fusion demonstrate how, historically, urban working-class Black men have developed community and practiced self-care through the contested adoption of Asian martial arts practice. By zeroing in on this rich but heretofore understudied vein of American cultural exchange, Price not only broadens the scholarship around sites of empowerment via such exchanges but also offers a compelling example of nonessentialist liberation for the twenty-first century.